Case Report: Proximal bronchial injury in small-cell lung cancer patient after moderately hypofractionated radiotherapy - Zhang, Tongsong; Wang, Yun; Wang, Haiqing; Yan, Chao; Dai, Chengcheng; Qu, Linli; Yang, Tao; Yang, Aijie (Frontiers in Oncology, 2025)
BackgroundProximal bronchial injury is a frequently observed complication in patients with central lung cancer following high-dose stereotactic body radiotherapy, whereas it is rarely reported after moderately hypofractionated radiotherapy. In this article, we present a case of proximal bronchial injury in a patient with small-cell lung cancer after moderately hypofractionated radiotherapy.Case presentationA 45-year-old male patient with no history of smoking was diagnosed with limited stage small-cell lung cancer. According to guidelines of the National Comprehensive Cancer Network, the patient was treated with chemoradiotherapy, which included etoposide and cisplatin as well as radiotherapy at a dose of 65 Gy/26 fractions. Three months after radiotherapy, the tumor disappeared; however, stenosis of the right main bronchus, right upper lobe bronchus, and intermediate bronchus, as well as atelectasis of the right upper and middle lobes, occurred and gradually worsened. Anti-infection and hormonal therapy were ineffective. One year after radiotherapy, grade 3 damage was formed in the proximal bronchus according to the Common Terminology Criteria for Adverse Events (version 5.0). Following endoscopic balloon dilatation of the right main bronchus, asthma symptoms of the patient were reduced.ConclusionThis case reminds us that it is necessary to implement a proximal bronchial dose constraint and prevent the occurrence of dose hot spot in the proximal bronchus when administering moderately hypofractionated radiotherapy with a physical dose exceeding 65 Gy.